Private screenings: Ingmar Bergman's 'Cries and Whispers' and cinematic fiction. Issue 10 (3rd October 2021) - Thompson, Lucas
ABSTRACT: Though literary studies has developed a rich understanding of the way that certain Modernist, early-, and mid-twentieth-century writers responded to cinematic conventions in their work, and to a lesser extent postmodern novelists as well, we do not have a full account of how contemporary fiction is responding to the visual norms embedded within cinema, nor how readers intimately familiar with filmic form might be experiencing these novels. By reconsidering film and literature in light of the groundbreaking work on the literary imagination done by Elaine Scarry in Dreaming by the Book, this article isolates a strand of criticism from recent decades that asks very different questions of literature to those usually asked by film theorists, cultural studies critics, and philosophers interested in the subject. Via a detailed examination of Ingmar Bergman's overtly cinematic short story, 'Cries and Whispers', which serves as an unusually direct instance of the multiple connections between literary and cinematic visuality, the article opens up broader questions about the ethics of seeing, and the ways in which contemporary fiction – and indeed twentieth-century fiction more broadly – might be understood in relation to cinema.